Genius Hour: an innovative methodological strategy in the Spanish as a Foreign Language class - Bieger Morales, Clara; Caballero-García, Presentación Ángeles (Didáctica. Lengua y Literatura, 2019)
This work proposes to use Genius Hour, an idea that originated in a business environment, as an innovative teaching and learning strategy in the Spanish as a Second Language (SSL) class. Genius hour falls within the category of Project-Based Learning (PBL), where inquiry plays a fundamental role. This work will focus on a multicultural secondary school context. Throughout it, basic aspects on how to implement this strategy are described, as well as its expected pedagogical benefits. Lastly, possible future work ideas are presented. We suggest carrying out an empirical study to confirm the theoretical outcomes predicted by this proposal.